2020
DOI: 10.3390/su12197983
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Indigenous Peoples in the Context of Resource Management in Relation to Climate Change in Southeast Asia

Abstract: In this article, we document how four indigenous peoples in insular Southeast Asia (Indonesia and the Philippines) have reacted to external interventions and discuss to what extent climate change has been a factor in the adjustment of their way of life. All groups share a similar environment, that is tropical low land rainforest. However, their traditional modes of exploitation of this environment vary, which can be ascribed to specific geographical and cultural characteristics. In recent years, these indigeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In line with the above guidelines, as well as following additional principles for working with forest-dependent communities (Persoon and Minter 2011), in each research site consent was first sought from the relevant customary authorities, usually the village chief and clan leader. In some cases, they decided to call residents together, in order for the principal researcher to explain the aims and process of the study, and for people to ask further questions.…”
Section: Methodsmentioning
confidence: 99%
“…In line with the above guidelines, as well as following additional principles for working with forest-dependent communities (Persoon and Minter 2011), in each research site consent was first sought from the relevant customary authorities, usually the village chief and clan leader. In some cases, they decided to call residents together, in order for the principal researcher to explain the aims and process of the study, and for people to ask further questions.…”
Section: Methodsmentioning
confidence: 99%
“…Restricted to disadvantaged groups and scarce government resources for a long time, few studies in Taiwan focus on IPPOs, even though the universal interests in indigenous people knowledge has attracted much attention (Ngulube and Lwoga, 2007;Persoon and Minter, 2020). Among the recent publications (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) from the Journal of the Taiwan indigenous Studies Association, we found only two studies from business perspectives (Fan, 2015;Lin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to indigenous people in south-east Asia, Papuans discovered that transformation from traditional to modern society is complicated. 27 In line with this, modernism leads to conditions completely different to that from the past, and it is a complex process. 28 Papuans found that their longstanding cultural practices must be incorporated into a more modern way of living.…”
Section: Discussionmentioning
confidence: 94%